2017
DOI: 10.1007/s10853-017-0983-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanical properties of free-standing multiwalled carbon nanotube paper prepared by an aqueous mediated process

Abstract: Free-standing carbon nanotube film (bucky paper) is a very important material for various applications, but its commercial production is still limited due to size, cost and properties. In the present work, different methods are used to prepare five different types of bucky papers, namely normal, pure refluxed, oxidized, oxidized refluxed and functionalized by using as-produced multiwalled carbon nanotubes (MWCNTs), refluxed MWCNTs, air-oxidized MWCNTs, oxidized refluxed MWCNTs and HNO 3 functionalized MWCNTs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, Figure 3e shows the σ f of BPs treated by PAMAM in our study is much higher than that of various CNT‐functionalized BPs prepared by other solution methods. [ 8,9,12,14,21,24–30 ] To further explore the internal stress‐transfer mechanisms, we investigated the fracture surfaces of tested samples (Figure 3f–h) and found that the fracture surfaces of PGBPs were very jagged while they were relatively flat for PBPs and CFBPs. This observation again indicated that the capability to resist crack propagation was enhanced due to the introduction of the PAMAM‐induced chemical cross‐linking at the interfaces between CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Figure 3e shows the σ f of BPs treated by PAMAM in our study is much higher than that of various CNT‐functionalized BPs prepared by other solution methods. [ 8,9,12,14,21,24–30 ] To further explore the internal stress‐transfer mechanisms, we investigated the fracture surfaces of tested samples (Figure 3f–h) and found that the fracture surfaces of PGBPs were very jagged while they were relatively flat for PBPs and CFBPs. This observation again indicated that the capability to resist crack propagation was enhanced due to the introduction of the PAMAM‐induced chemical cross‐linking at the interfaces between CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Additionally, their large strength-to-weight ratio is an added value for the formation of freestanding films, an extremely important parameter in bolometer (BM) technology. 1,3,13 From the viewpoint of practical implementation, these nanotubes are compatible with silicon (Si) microfabrication technology and have also displayed strong promises toward a disruptive technology. [14][15][16] All these exceptional properties offer its prospects for future device applications.…”
Section: Introductionmentioning
confidence: 99%